Originally posted by arvind@Nov 9 2004, 05:29 AM
hi,
as far as part b is concerned here is the proof:
A+ A'B +A'B' = A + A' ( B + B' ) = A + A' = 1
because by demorgan laws, A + A' =1
part a is not clear what is that emoticon doing in between? B)
[post=3479]Quoted post[/post]
Thread starter | Similar threads | Forum | Replies | Date |
---|---|---|---|---|
R | Boolean algebra simplification | Homework Help | 22 | |
V | Boolean algebra excercises | Homework Help | 2 | |
Digital Electronics | Homework Help | 1 | ||
Solving boolean expression using annihilation rule | Homework Help | 1 | ||
I | Deriving Product of Sum from circuit (decoder + AND gate) | Homework Help | 2 |